Audit Decisions: The Impact of Interactive Reviews with Group Support System on Information Ambiguity - Utami, Intiyas; Nahartyo, Ertambang (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research paper Research aims: This paper examines the impact of interactive reviews and the effectiveness of group support system (GSS) in mitigating information ambiguity in audit decisions. Design/ Methodology/ Approach: The research employed a laboratory experiment, with 74 students serving as subjects. In this study, the following information ambiguity were manipulated: (1) insufficient and complex data, (2) sufficient and complex data, or (3) sufficient and non-complex data. The decision-making process (individually and through GSS interaction) was also manipulated. In this research, audit decisions made of the client’s internal control system served as the dependent variable. Research findings: Analysis shows that ambiguity level has a negative effect on the accuracy of audit decisions. The empirical evidence acquired suggests that GSS-based interactive review increases the accuracy of audit decisions. It further shows that the GSS-based interactive review can be effective and practical as a strategy to mitigate information ambiguity in the audit decision making process during the planning stage. Theoretical contribution/ Originality: By investigating the benefits of information technology as a control mechanism for the auditing process and by looking at how it alters auditors’ behaviour and how it enables the auditing team to behave in reviewing their work, this study contributes to extant literature. This research fills in the theoretical gap by using GSS to mitigate the ambiguity of information. Practitioner/ Policy implication: The result of this study will encourage auditor to use GSS as a means of communication between the audit team leader and members. Research limitation/ Implications: The limitation of this study lies in its using a single leader and not other members of the audit team to do the GSS in the experimental manipulation. Keywords: Audit Decisions, Experimental Research, Group Support System, Information Ambiguity JEL Classification: M42